KONTEKSTUALISASI PRAKTIK ZUHUD BAGI KAUM PROFESIONAL - Muhammad Muhammad (UIN Sumatera Utara, 2019)
The relevance of Sufism in modern human life confirms the importance of Sufism in the dimensions of modern society's life, because sufism can color all activities that have social, political, economic and national cultural dimensions. Sufism can be practiced by every Muslim, from any social layer and any where. Sufism is present in an interesting form primarily by emphasizing continuity rather than a change in the beliefs and practices of local religious traditions.